Synthesis and biological activity of Аcinetobacter calcoaceticus IMV B-7241 surfactants depending on monovalent cations content in cultivation medium - Pirog, Tatiana; Lutsay, Dariya; Shevchuk, Tetiana; Iutynska, Galyna (My University, 2021)
Microbial surfactants (biosurfactants) are multifunctional preparations due to a combination of physicochemical (reduction of surface and interfacial tension, emulsifying activity) and biological (antimicrobial and antiadhesive activity, the ability to destroy biofilms) properties. However, the disadvantage of biosurfactants synthesized as a complex of compounds is the possibility of changing the biological activity depending on the conditions of producer cultivation. Aim. To study the effect of potassium and sodium cations on the NADP+-dependent glutamate dehydrogenase activity of cell-free extract of Acinetobacter calcoaceticus ІМV B-7241 with subsequent appropriate modification of the nutrient medium composition and determination of antimicrobial and anti-adhesive activity of surfactant synthesized. Methods. A. calcoaceticus ІМV B-7241 strain was grown in media containing 2% of sunflower oil waste as a carbon source, as well as various concentrations of potassium and sodium chloride (basal – 1.0 g/l NaCl, medium # 1 that did not contains NaCl, medium # 2 in which the concentration of NaCl was 2.0 g/l, medium # 3 in which the concentration of NaCl and KCl was 1.0 g/l each). The surfactants were extracted from the supernatant liquid culture with a modified Folch mixture. Anti-adhesive activity and the degree of biofilms degradation were determined by spectrophotometric method, antimicrobial activity − by the indicator of the minimum inhibitory concentration (MIC). Activity of enzymes of surface-active aminolipids biosynthesis (NADP+-dependent glutamate dehydrogenase) and glycolipids (phosphoenolpyruvate (PEP) carboxylase, PEP-synthetase, PEP-carboxykinase, trehalose phosphate synthase) were analyzed in cell-free extracts obtained after the destruction of cells by ultrasound. Results. It was found that potassium and sodium cations in concentrations of 50 and 100 mM are inhibitors of NADP+-dependent glutamate dehydrogenase, and in lower concentrations (5–20 mM) – activators of this enzyme, as well as PEP-carboxykinase and PEP-synthetase. The increase in the biosurfactant concentration to 6.1−7.7 g/l during cultivation of A. calcoaceticus ІМV B-7241 in medium # 1 and # 3 was due to the predominant synthesis of glycolipids under such conditions, which was evidenced by the increase in 1.8−6.5 times in the activity of PEP-carboxylase, PEP-carboxykinase, PEP-synthetase and trehalose phosphate synthetase compared to the indicators on the basal medium. The concentration of surfactants synthesized in the basal medium was 3.6 g/l, but such surfactants were characterized by the highest antimicrobial and anti-adhesive activity. Their MIC against the test-cultures of studied bacteria (Pseudomonas sp. MI-2, Bacillus subtilis BT-2, Escherichia coli IEM-1, Staphylococcus aureus BMS-1, Enterobacter cloaceae C-8) and fungi (Candida albicans D-6, Rhizopus nigricans P1, Aspergillus niger P-3, Fusarium culmorum T-7) were 0.88−56 μg/ml and were by 2−3 orders of magnitude lower compared to established for surfactants synthesized in modified media # 1–3. In the case of treatment of abiotic materials with surfactant solutions obtained on the basal medium, the adhesion of bacteria and fungi was on average 10–20 % lower than after surface treatment by the surfactant synthesized in modified media. In the presence of 148−296 μg/ml of surfactants obtained in the basal medium, destruction of S. aureus BMS-1 and B. subtilis BT-2 biofilms was 45−66 %, and C. albicans D-6 yeast – 39−44 %. Under the action of similar concentrations of surfactants synthesized in modified media, the destruction of bacterial and yeast biofilms was lower: 6-52 and 20–46 %, respectively. Conclusions. The obtained results are consistent with the data of our previous studies on the possibility of regulating the antimicrobial and antiadhesive activity of surfactants in the process of producer cultivation by changing the content of cations in the medium, which are inhibitors/activators of enzymes responsible for the synthesis of components of the surfactants complex, which have certain biological properties.
Keywords: поверхнево-активні речовини; катіони калію і натрію; біологічна активність; біосинтез; кафедра біотехнології і мікробіології; Acinetobacter calcoaceticus ІМВ В-7241; surfactants; potassium and sodium cations; biological activity; biosynthesis